Moral issues about certain interventions on human foetuses/embryos - Tettamanzi, Dionigi (Medicina e Morale, 2024)
Interventions on the human foetus are certainly not of today. Today, however, they pose new and more serious problems from various points of view, not least the ethical one. The increasing development of prenatal medicine has expanded knowledge through diagnostic means and, at the same time, opened the way for in utero therapy. Human foetuses, also as a result of the spread of provoked and legally permitted abortions, have increasingly become possible 'donors' of organs and tissue.